Investigating a New Psychological Variable in Second Language Acquisition: Comparing Social Identity Across Canadian French Education Programs - Walton, Hilary (Frontiers in Education, 2022)
This study investigates social identity as a potential psychological variable in second language education. Despite the fact that school plays a critical role in the formation of social identity for students, social identity has yet to be studied across educational contexts. Thus, this study investigates social identity differences across three groups of learners enrolled in French as a second language programs in Ontario, Canada: core French, extended French and French immersion, to determine whether students’ membership in a particular language program influences their social identity. Sixty high school students registered in these programs completed a validated measure of social identity (i.e., Ingroup Identification Questionnaire) and answered several open-ended questions about student dynamics within and between French programs. Results confirm that there are statistically significant differences in social identity between all programs. Findings suggest that French immersion students have the highest level of social identity associated with their French program, followed by extended French and lastly, by core French students. This corresponds to the amount of class time that students spend in program-specific classes with their same-program peers. Qualitative findings suggest that French immersion and extended French students are aware of ingroup-behavior, experience a bond with their same-program peers and, in some cases, perceive a division with students enrolled in other programs, while the same is not true for core French students. These dynamics between students enrolled in different French programs provide further evidence for the formation of education program-based social identities. This is one of the few studies to measure social identity in educational settings and the first study to compare the social identities of second language learners. Its findings may be used to help future studies examine group-level behaviors resulting from social identity in various educational contexts and support social identity as a psychological variable that merits further attention in education research.